-6y+9x=y-x+2

Simple and best practice solution for -6y+9x=y-x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6y+9x=y-x+2 equation:


Simplifying
-6y + 9x = y + -1x + 2

Reorder the terms:
9x + -6y = y + -1x + 2

Reorder the terms:
9x + -6y = 2 + -1x + y

Solving
9x + -6y = 2 + -1x + y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
9x + x + -6y = 2 + -1x + x + y

Combine like terms: 9x + x = 10x
10x + -6y = 2 + -1x + x + y

Combine like terms: -1x + x = 0
10x + -6y = 2 + 0 + y
10x + -6y = 2 + y

Add '6y' to each side of the equation.
10x + -6y + 6y = 2 + y + 6y

Combine like terms: -6y + 6y = 0
10x + 0 = 2 + y + 6y
10x = 2 + y + 6y

Combine like terms: y + 6y = 7y
10x = 2 + 7y

Divide each side by '10'.
x = 0.2 + 0.7y

Simplifying
x = 0.2 + 0.7y

See similar equations:

| 2x+4-x=11 | | 25+(0.12x+100)=29.46 | | -6y^2-y=-1 | | 3(x-2+2x-5x-7)=0 | | 8*x+6=-2x-14 | | 100=20logx | | 320(3/4)2 | | 3500+145.50x=6410 | | 1/7n=−4 | | 3x+5h-2=12 | | -6d+15=3(y-1) | | -7(2n+3)=-7 | | x-0.22x=500.76 | | 72(3/4) | | n/8=2/3.2 | | 3y+5x=11 | | 3m-5+8m=17 | | 56+a+a^2=0 | | 56+a+a^2=0 | | 9/20=7.2/h | | 9/20=7.2/h | | 10(s-3)=-83 | | x-0.2x=498.20 | | x^6-6x^5+9x^4=0 | | (c-1)(-8c^2+c-5)= | | b/17.6=1/8.8 | | 5(n+3)=5 | | 7/9-7=-5 | | T=6-t | | 5d^2+20d+20=0 | | -1/8(4/5x-24)= | | 20.50x+395=1112.50 |

Equations solver categories